Under the sign of consumption - Scaricabarozzi, Rossana (Orientación y Sociedad.)
The series of enunciations exposed in this work attempts to establish a conceptualization of consumption in relation to the communication and reception processes of symbolic goods. In addition, it will attempt to account for some possible derivations of the problem in question. The article explores different definitions penned by diverse authors seeking to set out the essential aspects concerning the object of study Thus, consumption becomes a space within which the appropriation of material and symbolic goods, social differentiation and symbolic class distinctions, integration, communication, amongst other things, take place. Despite the fact that none can sufficiently explain all the peculiarities related to consumption practices, all offer enriching insights that help us understand the concept we are dealing with. This is why the purpose of the present formulation is to reflect from another perspective, stressing the particularisms. And, in this way, to begin to lift the veil that conceals the forces of the social matrix